Encapsulation of Bixin with High Amylose Starch as Affected by Temperature and Whey Protein - Pérez-Monterroza, Ezequiel José [UNESP]; Chaux-Gutiérrez, Ana María [UNESP]; Franco, Célia Maria Landi [UNESP]; Nicoletti, Vânia Regina [UNESP] (Springer Nature, 2018)
Microencapsulation of bixin using high-amylose corn starch was carried out by the acidification method. Bixin powders were characterized by differential scanning calorimetry (DSC), X-ray diffractometry (XRD), FT-IR spectrometry, color parameters, encapsulation efficiency, bixin release profile. In addition, the effect of whey protein (WP) on the microencapsulation process was investigated. The results obtained from DSC, X-ray diffraction and FT-IR spectrometry indicated that only in the samples prepared at 90 °C (B0WP90°C, B10WP90°C, and B20WP90°C) there was formation of crystalline structures, with melting temperatures at 117.2°, 105° and 104 °C, respectively. The possible interactions between bixin, WP and amylose starch are also discussed.
Keywords: Annatto; Melting enthalpy; Microencapsulation; Release characteristics